Occupational Exposures and Metabolic Syndrome Among Hispanics/Latinos: Cross-Sectional Results From the Hispanic Community Health Study/Study of Latinos (HCHS/SOL). Issue 11 (November 2017) - Bulka, Catherine M.; Daviglus, Martha L.; Persky, Victoria W.; Durazo-Arvizu, Ramon A.; Avilés-Santa, M. Larissa; Gallo, Linda C.; Hosgood, H. Dean; Singer, Richard H.; Talavera, Gregory A.; Thyagarajan, Bharat; Zeng, Donglin; Argos, Maria
Abstract : Objective: We assessed the cross-sectional relationships of self-reported current occupational exposures to solvents, metals, and pesticides with metabolic syndrome and its components among 7127 participants in the Hispanic Community Health Study/Study of Latinos. Methods: Metabolic syndrome was defined as a clustering of abdominal obesity, high triglycerides, low high-density lipoprotein cholesterol, high blood pressure, and/or high fasting glucose. Regression models that incorporated inverse probability of exposure weighting were used to estimate prevalence ratios. Results: Solvent exposure was associated with a 32% higher prevalence of high blood pressure (95% confidence interval: 1.09 to 1.60) than participants not reporting exposure. No associations were observed for occupational exposures with abdominal obesity, high triglycerides, low high-density lipoprotein, or metabolic syndrome. Conclusion: Our findings suggest that solvent exposure may be an important occupational risk factor for high blood pressure among Hispanics/Latinos in the United States. Abstract : Supplemental Digital Content is available in the text